Rhinobatos manai sp. nov., a new species of guitarfish (Rhinopristiformes: Rhinobatidae) from New Ireland, Papua New Guinea - White, William T.; Last, Peter R.; Naylor, Gavin J.p. (Zootaxa, 2016)
A new species of guitarfish (Rhinobatos) is described based on a single specimen collected in 2014 from off New Ireland in Papua New Guinea. This specimen represents the first record of the family Rhinobatidae in Papua New Guinean waters. Based on molecular data, the new species appears to be most similar to Rhinobatos whitei (Philippines) and Rhinobatos sainsburyi (northern Australia), but is distinguished based on its coloration, morphology and certain meristic characters.